EFFECT OF EDUCATION, TRAINING, MOTIVATION AND WORK SATISFACTION ON BANKING ORGANIZATION COMMITMENTS - nasfi nasfi (Jurnal Ipteks Terapan, 2020)
This study aims to reveal: 1) the effect of education and training (training) on organizational commitment to banking, 2) the influence of work motivation on organizational commitment to banking, and 3) the effect of job satisfaction on banking organizational commitment.The study population was employees of PT. Bank Perkreditan Rakyat (BPR) Rangkiang Aur Denai, the office of the Bukittinggi City working area and the Payakumbuh City working area. With the number of bank offices 8 (eight) offices and the number of employees 63 people and all have attended education and training. The sample was taken using proportionate random sampling technique using the Slovin formula, so the size of the sample in this study were 54 samples divided into several sections in the offices of PT. Bank Rangkiang Denai. The analytical tool used is multiple linear regression using the SPSS (Statistical Package For Social Science) program.The results of this study are: 1) training has a significant and positive effect on organizational commitment at PT. Bank Rangkiang Denai. 2) Work motivation has a significant and positive effect on organizational commitment at PT. Bank Rangkiang Aur Denai. 3) Job satisfaction has a significant and positive effect on organizational commitment at PT. Bank Rangkiang Aur Denai.